Endocardite infecciosa em pequenos animais - Melanchauski, Mariana Serrano [UNESP] (2011)
Infective endocarditis is a process in which an infection attacks the heart endothelial surface, and is commonly caused by bacterial colonization, which is called bacterial endocarditis. It is a condition rarely found in dogs and cats, and is more prevalent in male dogs of large size. It mainly affects the left side of the heart, affecting the mitral and aortic valves with greater frequency. The circulation of the bacterium in the bloodstream is what gives rise endocarditis, and is caused by any non-aseptic process that serves as a gateway for bacterium in the body, as from a skin lesion, even as an invasive procedure, such as, catheterization and surgery. The ante-mortem diagnosis is difficult because the clinical signs of endocarditis are varied and common to other diseases, summing up the signs of infection (fever, lethargy, weight loss), and presence of heart murmur and may show signs of congestive heart failure. Thus, the diagnosis is most often through autopsy. To arrive at a diagnosis should be used, besides the history and physical examination, some laboratory tests, especially blood cultures and echocardiography. Treatment is accomplished through the use of antibiotics for long period of time, it is very important to follow the results of susceptibility after its outcome is revealed. The prognosis for bacterial endocarditis ranges from guarded to poor, and can be assessed mainly by the echocardiography. There are few studies in veterinary about the bacterial endocarditis, and the majority is case reports